Research Progress on Effects of Antifreeze Components, Nanoparticles and Pre-Curing on the Properties of Low-Temperature Curing Materials - Xianhua Yao; Mingduo Wan; Yongsheng Zhu; Lihua Niu; Xiaoxiang Ji; Shengqiang Chen; Wei He; Linyan Han (Buildings)
There are long periods of winter construction in China’s eastern and western Alpine regions. The decreased construction temperature adversely affects the workability, mechanical properties, and durability of cement-based materials and alkali-activated materials. Under low-temperature curing conditions, the hydration reaction of these materials slows down, resulting in limited strength development and reduced durability. In response to this problem, researchers have summarized three measures to improve performance: the use of anti-freezing components, nanoparticles, and pre-curing. The effects of anti-freezing components on the mechanical properties and micro-mechanism changes of Portland cement, sulphoaluminate cement, magnesium phosphate cement-based materials, and alkali-activated cementitious materials are organized. Additionally, the improvement of macro-micro properties in cement-based materials through mineral admixtures, nanoparticles, and hydrated calcium silicate seeds is summarized. The influence of pre-curing on the mechanical properties of cement-based materials is analyzed, focusing on the relationship between pre-curing time and the critical strength of frost resistance. Finally, existing research challenges are summarized, and future research directions are proposed, providing valuable references for the further development of materials and engineering applications.